Development of Semi-Static Steam Process for the Production of Sludge-Based Adsorbents - Yehya A. El-Sayed; Kevin F. Loughlin; Saeed ur Rehman; Dana Abouelnasr; Isam Al-Zubaidy (Adsorption Science & Technology)
In this study, a specially developed unique process was used to prepare sludge-based activated adsorbents (SBAs) from municipal sewage sludge collected from a wastewater treatment plant in Sharjah. A reaction chamber is designed to allow the carbonization and activation of sewage sludge in a saturated steam environment generated inside the chamber (semi-static). The semi-static steam process is carried out in the absence of any external gas flow into the reaction chamber. The activated sample is subjected to acid treatment. Other SBA samples are also prepared at the same temperatures using a conventional method in the presence of external flow of nitrogen gas. The surface chemistry for the SBA samples is characterized using Boehm titrations, pH measurement, ash content and scanning electron microscope integrated with energy-dispersive spectroscopy (EDAX). The semi-static steam method results in the formation of an SBA sample with acidic surface and higher carbon content as compared with the samples prepared by the conventional method. The metal contents of the SBAs are significantly different and depend on the methods of preparation. Nitrogen sorption isotherms are measured and used for the analysis of structure and porosity. The BET surface area for the SBA sample produced in the proposed method is calculated to be 838 m 2 /g. The SBA samples are then compared for adsorption efficiency of lead ions from aqueous solution, which is observed to be dependent on the microporosity and surface basicity.